2006
DOI: 10.1007/s11154-006-9017-x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and leptin: Potential tools in the differential diagnosis of pediatric diabetes?

Abstract: The incidence of type 1 and type 2 diabetes mellitus in the pediatric population has increased over the past decade. The practitioner is often faced with the challenge of differentiating between type 1 and type 2 diabetes at the time of initial diagnosis because of the overlap of clinical and laboratory characteristics between these two entities. Adipokines are proteins secreted by the adipose tissue. Leptin and adiponectin are two adipokines that have been extensively studied in vitro, in animal studies, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 119 publications
(205 reference statements)
0
11
0
9
Order By: Relevance
“…Thus, increased resistin in type 1 DM patients seems to be suggestive of subclinical atherosclerosis. Because serum resistin levels are generally unrelated to markers of insulin resistance 15,16 and the association of adiponectin and leptin with insulin resistance seems to be more evident, 5,6,9,10 the sole relationship of resistin with CIMT in this population of type 1 DM patients raises a question about the association of insulin resistance with macrovascular complications.…”
mentioning
confidence: 94%
“…Thus, increased resistin in type 1 DM patients seems to be suggestive of subclinical atherosclerosis. Because serum resistin levels are generally unrelated to markers of insulin resistance 15,16 and the association of adiponectin and leptin with insulin resistance seems to be more evident, 5,6,9,10 the sole relationship of resistin with CIMT in this population of type 1 DM patients raises a question about the association of insulin resistance with macrovascular complications.…”
mentioning
confidence: 94%
“…In contrast to type 2 diabetes, involvement of adipose tissue in the low-grade systemic inflammation observed in T1DM has been investigated far less. Indeed, alterations in circulating levels of adipokines in T1DM indicate adipose tissue involvement in T1DM pathogenesis [8]. …”
Section: Introductionmentioning
confidence: 99%
“…10 On the other hand, it has been suggested that adiponectin increases tissue fat oxidation, leading to reduced levels of fatty acids and tissue triglyceride content, thus increasing insulin sensitivity. 11 Therefore, leptin and adiponectin with respective proatherogenic and antiatherogenic properties, and changes in their secretion or sensitivity may contribute to the development of type 2 diabetes and coronary artery disease; they can be important mediators linking adiposity and atherosclerosis to PCOS. 12 Recent studies highlight the importance of leptin-toadiponectin (L/A) and adiponectin-to-leptin (A/L) ratios related to obesity, IR, coronary artery disease, and stroke in different populations in Europe and Asia.…”
Section: Introductionmentioning
confidence: 99%